Novel Miscanthus hybrids: Modelling productivity on marginal land in Europe using dynamics of canopy development determined by light interception - Anita Shepherd; Danny Awty‐Carroll; Jason Kam; Chris Ashman; Elena Magenau; Enrico Martani; Mislav Kontek; Andrea Ferrarini; Stefano Amaducci; Chris Davey; Vanja Jurišić; Gert‐Jan Petrie; et al. (GCB Bioenergy, 2023)
Abstract New biomass crop hybrids for bioeconomic expansion require yield projections to determine their potential for strategic land use planning in the face of global challenges. Our biomass growth simulation incorporates radiation interception and conversion efficiency. Models often use leaf area to predict interception which is demanding to determine accurately, so instead we use low‐cost rapid light interception measurements using a simple laboratory‐made line ceptometer and relate the dynamics of canopy closure to thermal time, and to measurements of biomass. We apply the model to project the European biomass potentials of new market‐ready hybrids for 2020–2030. Field measurements are easier to collect, the calibration is seasonally dynamic and reduces influence of weather variation between field sites. The model obtained is conservative, being calibrated by crops of varying establishment and varying maturity on less productive (marginal) land. This results in conservative projections of miscanthus hybrids for 2020–2030 based on 10% land use conversion of the least (productive) grassland and arable for farm diversification, which show a European potential of 80.7–89.7 Mt year−1 biomass, with potential for 1.2–1.3 EJ year−1 energy and 36.3–40.3 Mt year−1 carbon capture, with seeded Miscanthus sacchariflorus × sinensis displaying highest yield potential. Simulated biomass projections must be viewed in light of the field measurements on less productive land with high soil water deficits. We are attempting to model the results from an ambitious and novel project combining new hybrids across Europe with agronomy which has not been perfected on less productive sites. Nevertheless, at the time of energy sourcing issues, seed‐propagated miscanthus hybrids for the upscaled provision of bioenergy offer an alternative source of renewable energy. If European countries provide incentives for growers to invest, seeded hybrids can improve product availability and biomass yields over the current commercial miscanthus variety.